The Putative E3 Ubiquitin Ligase ECERIFERUM9 Regulates Abscisic Acid Biosynthesis and Response during Seed Germination and Postgermination Growth in Arabidopsis . Issue 3 (8th May 2014) - Zhao, Huayan; Zhang, Huoming; Cui, Peng; Ding, Feng; Wang, Guangchao; Li, Rongjun; Jenks, Matthew A.; Lü, Shiyou; Xiong, Liming
Abstract : A wax locus negatively regulates ABA response within a small time window during seed germination and also affects ABA levels in seeds . Abstract: The ECERIFERUM9 ( CER9 ) gene encodes a putative E3 ubiquitin ligase that functions in cuticle biosynthesis and the maintenance of plant water status. Here, we found that CER9 is also involved in abscisic acid (ABA ) signaling in seeds and young seedlings of Arabidopsis ( Arabidopsis thaliana ). The germinated embryos of the mutants exhibited enhanced sensitivity to ABA during the transition from reversible dormancy to determinate seedling growth. Expression of the CER9 gene is closely related to ABA levels and displays a similar pattern to that of ABSCISIC ACID-INSENSITIVE5 ( ABI5 ), which encodes a positive regulator of ABA responses in seeds. cer9 mutant seeds exhibited delayed germination that is independent of seed coat permeability. Quantitative proteomic analyses showed that cer9 seeds had a protein profile similar to that of the wild type treated with ABA . Transcriptomics analyses revealed that genes involved in ABA biosynthesis or signaling pathways were differentially regulated in cer9 seeds. Consistent with this, high levels of ABA were detected in dry seeds of cer9 . Blocking ABA biosynthesis by fluridone treatment or by combining an ABA -deficient mutation with cer9 attenuated the phenotypes of cer9 . Whereas introduction of the abi1-1, abi3-1, or abi4-103 mutation could completely eliminate the ABA hypersensitivity of cer9, introduction of abi5 resulted only in partial suppression. These results indicate that CER9 is a novel negative regulator of ABA biosynthesis and the ABA signaling pathway during seed germination.